A Novel Classification System Based on Dissemination of Musculoskeletal Infection is Predictive of Hospital Outcomes. Issue 5 (May 2018) - Mignemi, Megan E.; Benvenuti, Michael A.; An, Thomas J.; Martus, Jeffrey E.; Mencio, Gregory A.; Lovejoy, Stephen A.; Copley, Lawson A.; Williams, Derek J.; Thomsen, Isaac P.; Schoenecker, Jonathan G.
Abstract : Background: Musculoskeletal infections (MSKIs) are a common cause of pediatric hospitalization. Children affected by MSKI have highly variable hospital courses, which seem to depend on infection severity. Early stratification of infection severity would therefore help to maximize resource utilization and improve patient care. Currently, MSKIs are classified according to primary diagnoses such as osteomyelitis, pyomyositis, etc. These diagnoses, however, do not often occur in isolation and may differ widely in severity. On the basis of this, the authors propose a severity classification system that differentiates patients based on total infection burden and degree of dissemination. Methods: The authors developed a classification system with operational definitions for MSKI severity based on the degree of dissemination. The operational definitions were applied retrospectively to a cohort of 202 pediatric patients with MSKI from a tertiary care children's hospital over a 5-year period (2008 to 2013). Hospital outcomes data [length of stay (LOS), number of surgeries, positive blood cultures, duration of antibiotics, intensive care unit LOS, number of days with fever, and number of imaging studies] were collected from the electronic medical record and compared between groups. Results: Patients with greater infection dissemination were more likely to have worse hospital outcomes for LOS, number of surgeries performed, number of positive blood cultures, duration of antibiotics, intensive care unit LOS, number of days with fever, and number of imaging studies performed. Peak C-reactive protein, erythrocyte sedimentation rate, white blood cell count, and temperature were also higher in patients with more disseminated infection. Conclusions: The severity classification system for pediatric MSKI defined in this study correlates with hospital outcomes and markers of inflammatory response. The advantage of this classification system is that it is applicable to different types of MSKI and represents a potentially complementary system to the previous practice of differentiating MSKI based on primary diagnosis. Early identification of disease severity in children with MSKI has the potential to enhance hospital outcomes through more efficient resource utilization and improved patient care. Level of Evidence: Level II—prognostic study.